Evaluation of the quality of endoscopically obtained esophageal biopsies in the dog - Münster, Michael; Vieth, M.; Hörauf, A. (Tieraerztliche Praxis Ausgabe Kleintiere Heimtiere, 2013)
Objective: An important premise for obtaining diagnostically relevant histology specimens is an appropriate biopsy technique. Goal of this study was to determine if biopsies of adequate quality can be obtained from the canine esophagus at the gastro-esophageal junction (GEJ) during routine upper gastrointestinal endoscopy. Material and methods: Over the course of one year, 58 dogs undergoing upper gastrointestinal endoscopy because of the presence of esophageal (n = 22) or gastrointestinal (n = 36) clinical signs were prospectively included. Five biopsies were repeatedly collected from the same dorsal and ventral locations of the GEJ, fixated individually in 4% neutral buffered formaldehyde, and evaluated histopathologically after standard preparation and haematoxylin and eosin staining. The presence of esophageal squamous epithelium with a basal cell layer and lamina propria mucosae in conjunction with foveolar columnar epithelium and cardiac glands, and the absence of fundic glands in one specimen, respectively, was judged as an adequately sampled biopsy. Results: Adequately sampled biopsies were reported in 45 out of 58 dogs, with 31 samples originating from the dorsal GEJ, 36 samples originating from the ventral GEJ, and with 22 samples originating from both sites, respectively. The incidence of adequately sampled biopsies increased significantly over time (r = 0,22; p < 0,05), with these biopsies being reported significantly more often during the last 6 months compared to the first 6 months of the study (p = 0,03). Histopathological evaluation of the esophageal squamous epithelium showed fibrosis, inflammation, elongation of the stromal papillae, and increased thickness of the basal cell layers in 14 out of 58 dogs. Stromal papillae of the ventral esophageal epithelium were significantly elongated in dogs with esophageal clinical signs compared to dogs with gastrointestinal clinical signs (p = 0,03). Conclusion and clinical relevance: After an initial learning phase adequate esophageal biopsies from the GEJ can be obtained in canine patients undergoing upper gastrointestinal endoscopy, and histological lesions can be found in these biopsies. © Schattauer 2013.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Canine; Gastro-esophageal junction; Gastroscopy; Histology; Morphometry; Specimen